The Effect of Slow Stroke Back Massage on Patients’ Anxiety Level - thomas ari wibowo; Suci Ariani (Universitas Nahdlatul Ulama Surabaya, 2022)
Anxiety is a feeling of fear or anxiety from negative thoughts, excessive negative emotions that play a role in causing illness. The purpose of this study was to determine the effect of Slow Stroke Back Massage on patient anxiety with various literatures obtained.The method used is Literature Review with database searches such as Google Scholar, Sage, Science Direct, and Pubmed. The journals used were 15 consisting of 6 national and 9 international journals. The results of the discussion of the Literature Review Analysis that 15 of the journals said there was a significant effect between Slow Stroke Back Massage in reducing anxiety. There is an effect of Slow Stroke Back Massage on reducing patient anxiety